Período anterior à interferência de corda-de-viola em cana-planta - Piza, Caio Spada de Toledo [UNESP] (2014)
Sugarcane has undergone a major change in the environment with the adoption of mechanized harvesting. One of the changes resulting from the presence of straw on the ground was the change in weed profile. In this scenario Ipomoea hederifolia L. grown in importance. The presence of this weed in the areas of mechanical harvesting can contribute to the occurrence of infestations after the reform of the sugarcane plantation. There is still no information about the interference that this kind of morningglory can have on cane plant cycle. The aim of this study was to determine the Period Prior to Interference (PAI) of a weed community that contains I. hederifolia as the main weed in relation to sugarcane variety 'SP81-3250’ in the cane plant cycle. Moreover, the goal was to determine the possible loss of productivity change and technological parameters (Pol and ATR). Phytosociological analysis of the weed community was performed with determination of parameters relative density (Der), relative frequency (FeR), relative dominance (DoR), importance value index (IVI) and relative importance (IR) with the objective to confirm the predominance of mornigglory. The experimental treatments consisted of increasing periods of presence in the early sugarcane cycle with a weed community with predominance of mornigglory, namely: 0, 0-15, 0-30, 0-45 , 0-60, 0-75, 0-90, 0- 120, 0-150, 0-180, 0-210, 0-270, 0-330 days after emergence. It was used a randomized block design with four replications. The test was conducted in the field, getting sowing I. hederifolia. Also, selective weeding were performed. The phytosociological analysis showed that the community possessed predominance of mornigglory. The data showed that the PAI of mornigglory (I. hederifolia) relative to sugarcane 'SP81-3250' in the cane plant cycle was 76 days, with a level 5% for acceptable loss. The loss of productivity of industrialized stalks due to ...